All‐Optical Polarization‐Controlled Nanosensor Switch Based on Guided‐Wave Surface Plasmon Resonance via Molecular Overtone Excitations in the Near‐Infrared. Issue 19 (19th July 2020) - Karabchevsky, Alina; Hazan, Adir; Dubavik, Aliaksei
Abstract: Semiconductor transistors for sensors are considered the most widely manufactured device in history. Being invented to switch electronic signals they revolutionized electronics and paved the way for smaller and cheaper sensors, radios, calculators, and computers. However, electric switches are hampered by damage from very brief electrical and thermal effects or electromagnetic interference. For this reason, modern communication systems devote considerable attention to all‐optical switches, yet, the state‐of‐the‐art switching of photonic signals is fulfilled electronically. All‐optical switching allows light‐controls‐light through unique optical effects. Here, an all‐optical sensor switch, engineered to operate at telecommunication wavelengths, caused by the excitation of molecular overtones in a hybrid plasmonic–dielectric configuration is demonstrated. This configuration possesses a unique property: to control the sensor switch with the polarization state of light for two different plasmonic modes to co‐exist while exciting a single overtone. Control of the sensor switch is realized by tuning the polarization of incident light from transverse magnetic (switch‐on) to transverse electric (switch‐off). This switch provides a miniature, affordable, and fast chip‐scale polarization‐activated sensor device for a wide range of applications from optics communication to all‐optical computing and sensing. Abstract : A real‐time all‐optical sensor switch based on polarization‐dependent molecular overtone transitions, which represents the most efficient photomolecular sensor device in the near‐infrared to date, is demonstrated. The overtone excitations are switched simply by changing the polarization of the incident beam. The discovery opens new avenues of chip‐scale polarization‐activated organic sensors compatible with the silicon photonics platform.